2020
DOI: 10.1136/bmj.m2322
|View full text |Cite
|
Sign up to set email alerts
|

The healthiness and sustainability of national and global food based dietary guidelines: modelling study

Abstract: ObjectiveTo analyse the health and environmental implications of adopting national food based dietary guidelines (FBDGs) at a national level and compared with global health and environmental targets.DesignModelling study.Setting85 countries.ParticipantsPopulation of 85 countries.Main outcome measuresA graded coding method was developed and used to extract quantitative recommendations from 85 FBDGs. The health and environmental impacts of these guidelines were assessed by using a comparative risk assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
339
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(357 citation statements)
references
References 61 publications
13
339
1
4
Order By: Relevance
“…All evidence hitherto points towards consumption of more fibre and more whole foods, including cereal grains. Springmann et al (2020) found that in all FAO-defined geographical regions, with the exception of North America, current intakes of whole grain foods should at least double compared with national dietary guidelines, and in the cases of WHO and EAT-Lancet guidelines, increase by 241% and 362% respectively. Adoption of dietary guidelines would lead to major reductions in the global burden of diet-related NCDs through increasing consumption both of cereals rich in DF, and necessarily of fruits, vegetables, pulses, nuts and seeds rich in both micronutrients and DF.…”
Section: The Dietary Contributions Of Cereal Foodsmentioning
confidence: 97%
“…All evidence hitherto points towards consumption of more fibre and more whole foods, including cereal grains. Springmann et al (2020) found that in all FAO-defined geographical regions, with the exception of North America, current intakes of whole grain foods should at least double compared with national dietary guidelines, and in the cases of WHO and EAT-Lancet guidelines, increase by 241% and 362% respectively. Adoption of dietary guidelines would lead to major reductions in the global burden of diet-related NCDs through increasing consumption both of cereals rich in DF, and necessarily of fruits, vegetables, pulses, nuts and seeds rich in both micronutrients and DF.…”
Section: The Dietary Contributions Of Cereal Foodsmentioning
confidence: 97%
“…A recent study of national dietary guidelines concluded that the dietary change that would have the biggest effect on reduction of non-communicable diseases, with the greatest reduction of greenhouse gases, would be to increase intake of whole grains. 6 In China, the biggest effect would probably result from switching from polished rice to brown rice. Again, this would represent a major cultural change.…”
Section: Increasing Intake Of Whole Grainsmentioning
confidence: 99%
“…Recently, the EAT-Lancet Commission on Healthy Diets from Sustainable Food Systems published a reference diet that integrates both healthy and sustainable nutrition [ 5 ]. Numerous countries have examined how to adjust their local environments and policies to meet those recommendations, including Israel [ 10 , 11 , 12 , 13 ]. Implementing these recommendations within public health policy is still an issue [ 2 , 14 ].…”
Section: Introductionmentioning
confidence: 99%